Pro Re Nata Antihypertensive Medications and Adverse Outcomes in Hospitalized Patients: A Propensity-Matched Cohort Study. Issue 2 (21st June 2021) - Mohandas, Rajesh; Chamarthi, Gajapathiraju; Bozorgmehri, Shahab; Carlson, Jeremy; Ozrazgat-Baslanti, Tezcan; Ruchi, Rupam; Shukla, Ashutosh; Kazory, Amir; Bihorac, Azra; Canales, Muna; Segal, Mark S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Physicians routinely order blood pressure (BP) medications on an as needed basis or pro re nata to control BPs in hospitalized patients. We hypothesized that treatment of inpatients, who do not have a hypertensive emergency, with the use of antihypertensive medication on an as needed basis could lead to adverse outcomes. Four thousand two hundred nineteen patients who received BP medications on an as needed basis in addition to scheduled antihypertensive medications were matched 1:1 using propensity matching to those who received only scheduled BP medications. Compared with the propensity-matched cohort, patients who received antihypertensive medications on an as needed basis were more likely to experience abrupt lowering of systolic BPs (odds ratio, 2.05 [95% CI, 1.56–2.71], P <0.001), acute kidney injury (odds ratio, 1.24 [95% CI, 1.09–1.42], P =0.002), and ischemic stroke (odds ratio, 8.5 [95% CI, 1.96–36.79]; P <0.001). The use of as needed antihypertensive medication was also associated with increased in-hospital mortality (odds ratio, 2.36 [95% CI, 1.26–4.41]; P =0.001) and an increase in the median length of stay (4.7 versus 2.9 days; P <0.001). In addition, ischemic events were more likely in those who had an abrupt drop in BPs, and the risk was increased in proportion to the number of doses of as needed BP medications administered. The use of as needed antihypertensive medication is associated with an abrupt drop in BPs, increased risk of ischemic events, in-hospital mortality, and longer length of stay. We suggest that the routine use of as needed antihypertensive medication should be discouraged.